Sustainable valuation of land for development. Adding value with urban planning progress. A Spanish case study. (March 2020) - Codosero Rodas, José Maria; Castanho, Rui Alexandre; Cabezas Fernández, José; Naranjo Gómez, José Manuel
Highlights: It must not consider urban expectations of unlikely realization. The land valuation method proposed use the discount free cash flow model, using the wacc as discount rate. The land achieves its maximum value when it is fully urbanized. The land for development value can assessment from function of adding value with urban planning progress. This function is an exponential graph. Abstract: This article presents a valuation model of land for development in a sustainable way, based on the design and execution of urban planning. Using this method, one can obtain, at any given point in time, the added value progress of the urbanization process. For each year during the plan's execution, the value of land has been estimated. The free cash-flow method was applied in order to estimate the land valuation of any given year. From the estimate for each of those years, and using regression analysis, the most suited value added function was obtained, for the increase of value across time up to the point of finalized, fully urbanized land. The results show that this is an exponential growth function, such that during the initial years the progress of valuation is slow, but it accentuates during final years of execution as the land becomes urbanized, at which point the land achieves maximum value.